colostomy with simultaneous sphincter and colostomy - Palma, Eduardo C. (Cirugía del Uruguay, 1978)
Case material comprises 41 observations in which the end of the caecum was used for simultaneous colostomy and ileostomy; this was achleved by displacing and exteriorizing out the caecum and distal end of last ileal loop, and opening wide the end of the caecum. The operation was well tolerated, evolutio. was good in 40 patients (97,6 % ) and there was one death ( 2,4 % ) . Total shunt of faeces was obtained, the colon no longer functioned and there was good autonomic ileo-cecal function with intermitent spaced discharge of faeces. This double enterostomy was used with good results as complementary associate surgery in 17 patients who underwent left colectomy due to cancer; and in 2 due to complicated sigmoiditis. Secondary death-rate was 12 o. The double enterostomy was also used with good results as an associate complementary operation, in 15 cases of grave intestine ccclusion - and in 5 cases of peritonitis accompanied by occlusion. Secondary mortality was 20 % and 40 % respectively. Simultaneous ileostomy with sphyncter and colostomy were used with good results in 2 cases of grave hemorrhagic ulcerous colitis that could not be treated medically. Once the patients had improved, total proctocolectomy was performed, the ileostomy with sphyncter was maintained and the patients healed. Colonization of last ileal loop resulted and the faeces were automatically discharged in 3 ar 4 daily periods.